A novel construct of an electrochemical acetylcholinesterase biosensor for the investigation of malathion sensitivity to three different insect species using a NiCr2O4/g-C3N4 composite integrated pencil graphite electrode. Issue 26 (7th June 2022) - Bilal, Sehrish; Nasir, Muhammad; Hassan, M. Mudassir; Rehman, Muhammad Fayyaz ur; Sami, Amtul Jamil; Hayat, Akhtar
Abstract : An innovative electrochemical assay has been established to determine pesticide sensitivity against acetylcholinesterase and possible toxicity against insects. The analytical efficiency of three common insect AChEs was determined through this method. Abstract : Herein, an electrochemical biosensor has been prepared to assess the sensitivity of an organophosphate insecticide, malathion, to acetylcholinesterase (AChE) enzyme of three insects including Apis mellifera (honeybee), Tribolium castaneum (red flour beetle), and Zootermopsis nevadensis (dampwood termite). A composite of nickel chromite (NiCr2 O4 ) and graphitic carbon nitride (g-C3 N4 ) was prepared and characterized for its morphological, chemical and electrical properties. The NiCr2 O4 /g-C3 N4 composite integrated pencil graphite electrodes were used to covalently immobilize insect AChE enzymes and amperometric response of bioelectrodes was determined through cyclic voltammetry. The prepared bioelectrodes exhibited high enzyme immobilization efficiency and electro-catalytic performance. The integrated bioelectrodes could efficiently detect malathion induced inhibition of insects' AChEs. The linear ranges for malathion were found to be 0.1–1.6 μM, 1–40 nM and 2–100 nM, and LODs were 2 nM, 0.86 nM and 2.3 nM for A. mellifera, T. castaneum, and Z. nevadensis, respectively. Additionally, the biosensing platform developed using A. mellifera AChE was found highly sensitive and effective for malathion recoveries from spiked wheat flour samples with high recovery rates. Moreover, the proposed method was adequately reproducible and selective. The results revealed that A. mellifera AChE is less sensitive to inhibition by malathion as compared to T. castaneum, and Z. nevadensis AChE. The experimental results were validated through computational docking of malathion with insect AChEs and the results were in correspondence to experimental outcomes. The proposed method can be a plausible alternate to conventional analytical methods to assess the pesticide sensitivity and toxicity of various compounds against insect enzymes.